Revision Multiligament Knee Reconstruction Surgery - Stuart, Michael B.; Woodmass, Jarret M.; Krych, Aaron J.; Levy, Bruce A.; Stuart, Michael J. (The Journal of Knee Surgery, 2020)
Failed multiligament knee reconstruction is a challenging problem due to recurrent pathologic laxity that is often associated with limb malalignment, meniscus deficiency, articular cartilage insufficiency, decreased motion, compromised bone stock, and a paucity of graft sources. Revision surgical indications and techniques require a comprehensive evaluation of the patient, injury and treatment factors along with a focused physical examination and advanced imaging. A stepwise treatment approach can be effective in the evaluation of revision surgery and also in setting realistic patient goals.
Keywords: multiligament; revision reconstruction; knee